Judicial Review of Safe Countries of Origin Designations in Czechia - Karolina Michková (Časopis pro Právní Vědu a Praxi)
The article thoroughly assesses one of the approaches towards judicial review of the safe country of origin mechanism. It focuses on the judicial review of safe country of origin designations. As will be shown on a case study of Czechia, there may be deficiencies in specific safe country designations that the courts have to address when considering administrative actions. Based on case-law analysis the article provides several criteria that should be considered during the judicial review and addresses some interpretative issues that may come into play.